The Importance of Writing an Appropriate Abstract for Postgraduate EFL Libyan Students (Journal of Humanitarian and Applied Sciences, 2020)
A careful examination of a number of dissertations written by some Libyan EFL postgraduate students, has shown that they have problems in writing abstracts. The problem lies in the fact that students include unnecessary information or exclude some essential information in their abstracts. The aim of the current paper is to shed light on the importance of writing an appropriate abstract for postgraduate EFL Libyan students. The data for this research was collected from some examples of inappropriate abstracts written by some EFL Libyan postgraduate students and from questionnaires distributed among some lecturers in postgraduate English Departments at the Libyan Academy, Tripoli University, Zawia University, Sabrata University, and Bengahzi University. The collected data was consistent with the hypothesis. The results of the present paper showed that students have some problems in writing dissertation abstracts. On one hand, they exclude some essential information from their abstracts and on the other hand, they include lengthy background information, or unnecessary details. This investigation contributed in highlighting an important area of writing research papers. The findings indicated that more attention should be paid to writing this important part of research papers.
Keywords: Abstract; Dissertation; postgraduate